Kesalahan-Kesalahan Siswa dalam Menyelesaikan Soal Cerita Sistem Persamaan Linear Dua Variabel Berdasarkan Prosedur Newman Ditinjau dari Jenis Kelamin Siswa Kelas VIII SMP Negeri 1 Wamena - Christine Mersi Rumpaisum (Jurnal Pustaka Cendekia Pendidikan, 2024)
This research is descriptive qualitative research with a case study method. The aim of this research is to analyze and describe the types of student errors in solving story problems on systems of linear equations in two variables based on the Newman procedure in terms of gender, to analyze and describe the factors that cause students' errors in solving story problems on systems of linear equations. two variables based on the newman procedure in terms of gender. The subjects in this research were 4 (four) students consisting of 2 (two) male students and 2 (two) female students selected from class VIIIE of SMP N 1 Wamena. The technique for selecting research subjects used was purposive sampling. Data collection was carried out using written tests and interviews. Testing the validity of the data using time triangulation and data analysis was carried out by data reduction, data presentation and conclusions. The research results showed that there were types of errors, namely reading errors, understanding errors, transformation errors, processing skills errors, and final writing errors in all male and female subjects. Errors in writing the final answer were errors made by all research subjects. Factors that cause errors in terms of gender include not understanding the concept of place value, being in a hurry when reading, the subject not understanding the meaning of the question because the question being asked is difficult, not being careful in answering and being in a hurry when doing it, not understanding how to make mathematical models and changing the information obtained into mathematical models, being in a hurry to solve the problem, not being careful in calculations, and because the previous solution process was hasty, forgetting, not understanding the problem, and being careless.